Evaluation of the effectiveness of elastomeric mount using vibration power flow and transmissibility methods - Arib Rejab M.N.; Abdul Shukor S.A.; Mohd Sofian M.R.; Inayat-Hussain J.I.; Nazirah A.; Asyraf I. (Institute of Physics Publishing, 2023)
Dynamics; Engine mountings; Flexible structures; Natural frequencies; Rubber; Stiffness; Structural design; Synthetic rubber; Vibration analysis; 2 degree of freedoms; Dynamic stiffness; Flexible receiver; High frequency HF; Low and high frequencies; Structure-borne noise; Vibration isolation systems; Vibration power flow; Electric load flow